COMBINING BUSINESS AND HERITAGE-BUSINESS PLAN FOR AN EDUCATION AND CONFERENCE CENTRE AT PAPPLEWICK PUMPING STATION - Raj, Vinith John (2010)
Papplewick Pumping Station (PPS) is a 19th Century Victorian water works that used two steam engines to supply water to Nottingham. Today, the two steam engines are still functional and the pumping station has been developed as a tourist attraction. PPS is also actively involved in water conservation education through the Water Education Trust (WET). The pumping station has a cafe and gifts stores and hires out its premises for wedding ceremonies. Papplewick also organises special events such as Steaming Weekends and a popular themed event called “the 40’s.” Although PPS is spread across 12 acres of landscaped gardens, it is constrained by the lack of a large enclosed area (meeting / banquet hall) for groups that want to attend WET programmes or couples who want to hire PPS for wedding receptions. The present economic climate also influenced PPS, which is supported by financial aid, to become financially self-sufficient. To meet these three objectives PPS considered setting up the PPS Education & Conference Centre. This report provides two schemes for PPS to meet its objectives. Plan A explores the setting up of a full-fledged conference centre with an investment of £276,845. Plan B suggests focusing on current revenue streams and identifies ways of increasing it. It also explores the possibility of using a marquee to cater to wedding receptions and WET’s education programmes. The report includes an industry overview for the weddings and conferences markets. It develops a SWOT analysis for PPS, Porter’s 5 Force analysis for the venues market in Nottingham, and includes research of 50 venues around Nottingham. This data and interviews of people in the hospitality sector ensured a broad perspective of the market PPS is seeking to tap and helped identify the demand for green and sustainable venues. Interviews with the PPS board Chairman Geoffrey Bond and Director Ashley Smart were useful in understanding the current operations and future plans of the pumping station. Based on this understanding, PPS developed the following mission for its venues business: As a concerned member of the community, PPS is committed to providing excellent service at our green venues with minimal environmental impact. Using Porter’s Generic Strategies Framework, a decision was made to choose the “Differentiation Focus”. It was decided that PPS would develop its competitive advantage by offering Green and Sustainable Venues, Great Service and Exclusivity of hiring out the entire premises. The report also provides an operations strategy, estimates manpower requirement and evaluates various layout options before selecting the most feasible option. Market-based pricing method is used for pricing the conference and wedding venues. In the financials, the start-up capital for Plan A is estimated at £276,845, including 3 months working capital. This is followed by an estimate of the number of events per year with a realistic estimate at 65 events in the first year and a 25% growth year-over-year. The report also considers a worst case scenario for Plan A of 38 events per year and a growth rate of 10% year-on-year. A detailed costing for events revealed that the average income from a conference was around £600, while an average wedding package - wedding ceremony and reception - could yield in excess of £1,920, excluding the average income of £520 per event from the bar. Two options were explored in financing the project. Possibility 1 assumed an equity of £26,845 and the remaining £250,000 to be raised through a 10-year loan at 9% interest per annum, making this a highly leveraged transaction. Detailed workings indicated that Possibility 1 would work well if the realistic estimates are achieved. However, in the worst case scenario, the company would be under severe financial stress and would need a fresh infusion of capital in year 2. Possibility 2 considered PPS would raise £276,845 for the Education and Conference Centre through internal savings, grants and donations. In this scenario, the interest burden is nil and the stress on PPS’ financials would be much lower, with cash break-even coming at sales of £82,802 in 2011 compared with sales of £177,812 in 2011 under Possibility 1. Plan B used the Ansoff Matrix framework and market penetration as a means to increase revenue. It therefore focused on increasing the number of visits per visitor in a year, increasing footfalls at the pumping station and increasing the spend per customer. The plan also explored the possibility of using themed events for market penetration and the use of a marquee for wedding receptions and WET’s education programmes. The start-up cost in Plan B is £95,906 – funded by equity capital of £20,906 and loan of £75,000 at 9% p.a. for a period of 10 years. The loan payment in relatively low at £950 per month and does not burden PPS’ financials. The market penetration strategy alone is expected to generate revenues of up to £108,000 in 2013. On evaluating both plans, it is recommended that PPS should take up the market penetration strategy to improve its revenues from current activities and use Plan B option of a marquee to cater to wedding receptions and WET programmes.